Cover Picture: Macromol. Theory Simul. 2∕2015. Issue 2 (February 2015) - Fürstenberg, Florian; Gurtovenko, Andrey A.; Dolgushev, Maxim; Blumen, Alexander
Abstract : Front Cover: The assumption of proportionality between the viscosity and radius‐of‐gyration branching indices, g' and g, is suggested on the basis of the proposal of Stockmayer and Fixmann and on the data of Kurata and Fukatsu as well as our own, rather than the exponential relation assuming the value of the branching exponent ε = 0.5, based on data of Zimm and Kilb. Further details can be found in the article by M. Netopilíkon page 80 .